1993
DOI: 10.1046/j.1365-2648.1993.18060941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of attitudes, subjective norms and perceived control on nurses’ intention to assess patients’ pain

Abstract: This study examines the underlying determinants of nurses' behaviour regarding the conduct of pain assessments. One hundred nurses in a variety of health care facilities were invited to complete an Attitude Intention Questionnaire based upon the theory of planned action which is an extension of the theory of reasoned action. Results provide some support for the theory of planned action, as nurses' intention to conduct pain assessment was shown to be predicted by attitude, subjective norms and perceived control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 17 publications
4
35
1
3
Order By: Relevance
“…In their work comprising focus group interviews with nurses, the participants demonstrated selectivity toward the use of physical cues in their diagnosis of acute pain. In an earlier study involving a survey methodology (Nash, Edwards, & Nebauer, 1993), nurses perceived that physical data such as abdominal guarding, changes in vital signs, and decreased motility were critical to acute pain assessment. On the other hand, verbal complaints of pain, altered facial expressions, and patients' requests for analgesia were minor defining characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In their work comprising focus group interviews with nurses, the participants demonstrated selectivity toward the use of physical cues in their diagnosis of acute pain. In an earlier study involving a survey methodology (Nash, Edwards, & Nebauer, 1993), nurses perceived that physical data such as abdominal guarding, changes in vital signs, and decreased motility were critical to acute pain assessment. On the other hand, verbal complaints of pain, altered facial expressions, and patients' requests for analgesia were minor defining characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Nash et al (1993) conducted a research on five public and private hospitals located in Australia. The result showed that the group effect of attitude towards the behavior, subjective norm and perceived behavioral control can significantly affect the nurses' intention to perform pain assessment.…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
“…In pain management area, the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB) explained 21% of the variation in nurses' intention to assess patients' pain (Nash, Edwards & Nebauer, 1993). Jurgens (1996) found that nearly 50% of the variance in behavioral intention to administer morphine was accounted for the TPB determinants.…”
mentioning
confidence: 99%
“…While reviewing the literature, the researchers encountered different methodologies utilized for belief elicitation, with some research using paper and pencil surveys (e.g., Crawley & Koballa, 1992;Nash, Edwards, & Nebauer, 1993;Sparks & Shepherd, 2002), some using focus group interviews (e.g., McCarty, Hennrikus, Lando, & Vessey, 2001;Millstein, 1996;Sheehan et al, 1996), and others using both (e.g., Harrison & Liska, 1994;Randall & Gibson, 1991).…”
Section: Introductionmentioning
confidence: 99%